Windows Phone Recipes A Problem-Solution Approach - Ferracchiati, Fabio Claudio; Garofalo, Emanuele; SpringerLink (Berkeley, CA Apress, 2011)
Windows Phone 7.5 (code-named Mango) marks a significant upgrade to Microsoft?s smartphone products. Packed with sophisticated new features and functionality, the device is a .NET developer?s dream, easily programmable using Silverlight, XNA and C#. Windows Phone Recipes utilizes a proven problem-solution approach, providing a concise guide to all the phone?s features in recipe book format. First, the problem you're facing is identified. Then, a clear explanation of the solution is given, supported by a fully-worked code sample that demonstrates the feature in action. All aspects of development, configuration, testing, and distribution are covered. You'll find recipes that unlock advanced user interface features, deal with data storage, integrate with cloud services, add media and location services, and much more. It's everything you'll need to put a professional polish on your Windows Phone 7.5 applications!
Introduction to Developing Windows Phone Applications Windows Phone Must Knows Windows Phone Execution Model The User Interface The User Interface With Expression Blend Gestures Sensors Media Management Isolated Storage In the Cloud Testing Windows Phone Applications Deploying your Application
Electronic reproduction.
Keywords: Smartphones -- Programming; Mobile computing -- Programming; Electronic books